PENGARUH SUPPLY CHAIN MANAGEMENT TERHADAP KEUNGGULAN BERSAING DAN KINERJA PERUSAHAAN PADA RUMAH SAKIT IBU DAN ANAK ERIA BUNDA PEKANBARU - Arif Khalif; Samsir Samsir; Daulay N Iwan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2020)
This study aims to determine the effect of Supply Chain Management on competitive advantage and company performance at Eria Bunda Mother and Child Hospital Pekanbaru. The population in this study includes employees of the logistics, marketing and general departments of Rumah Sakit Ibu dan Anak Eria Bunda Pekanbaru, totaling 106 people with a sample of 84 people. Primary data were collected with a questionnaire as an instrument to prove the results of the study, to test the hypothesis in this study using PLS (Partial Least Square) analysis with the help of the SMARTPLS program. The sample chosen in this study were 84 employees associated with the logistics, marketing and general departments. The results showed that: 1) there was a positive and significant effect of Suppy Chain Management on the performance of the Rumah Sakit Ibu dan Anak Eria Bunda Pekanbaru. 2) there is a positive and significant effect of Suppy Chain Management on the competitive advantage of Rumah Sakit Ibu dan Anak Eria Bunda Pekanbaru,. 3) there is a positive and significant competitive advantage on the performance of the Rumah Sakit Ibu dan Anak Eria Bunda Pekanbaru,. 4) there is a mediating role for competitive advantage in the influence of Suppy Chain Management on company performance at Rumah Sakit Ibu dan Anak Eria Bunda Pekanbaru.Keywords: Supply Chain Management, Competitive Advantage, Company Performance.